The attitudes of stakeholders on causes leading to cost overrun in high-rise building projects in Bangkok and surroundings - Som, Vannoeun; Suweero, Kittipong; Muengnoi, Wutthipong (Frontiers in Engineering Innovation Research, 2024)
This research aims to study the attitudes of stakeholders towards the causes of cost overrun, analyze the similarities or differences in the attitudes of stakeholders, and group causes of cost overrun in high-rise building projects. A survey using a questionnaire was conducted to collect data from contractors and consultants working on high-rise building construction projects in Bangkok and its surroundings. Simple random sampling was used to distribute a total of 160 questionnaires, and 144 were returned, resulting in a 90% response rate. Data were analyzed using frequency, percentage, relative importance index (RII), t-test, and factor analysis (FA). Results showed that the most important attitude among contractors is that materials costs increased during construction among consultants are mistakes in construction and rework. When analyzing similarities or differences in attitudes, it was found that the most important attitude among all stakeholders was similarities. The total 27 most important causes were grouped into nine categories: construction phase, communication, design, finance, labor, management, estimation, external, and material causes. This study helps to increase knowledge about the various causes of cost overruns in high-rise building construction projects in Bangkok and its surroundings, serving as a guide for management and planning in future construction projects.